Analysis of particular design methods for aging landscapes in residential areas / Xiangyun Wang ... [et al.] - Xiangyun Wang; Misni, Alamah Misni; Buyadi, Siti Nor Afzan; Sobbri, Nur Hidayah (UiTM Press, 2024)
With the rapid improvement of economic and social medical security in recent years, the global aging situation has deepened. At the same time, the elderly groups' demand for the healthy use of landscape environment has increased. This study analysed the characteristics of the elderly population and the use needs of age-appropriate landscapes. Based on the theories of design, landscape architecture, sustainable design, and the critical points of age-appropriate landscape design, this paper applies unique design methods for designing and constructing aging landscapes in residential areas. The characteristics analysis of elderly landscape design includes vertical and drainage design, barrier-free design, garden road traffic planning, planting design, and landscape sustainability. The results and analysis stated that in combination with the design methods, a comfortable, safe, ecologically sustainable, and liveable aging landscape space is a suitable design for the residential area, and the local cultural design concept can enhance the sense of belonging of the elderly. The findings will provide theoretical and practical guidance for the design and construction of residential landscapes with suitable ecological environments for the elderly.